2020
DOI: 10.1002/lsm.23347
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Induced Vasospasm‐Evaluation of Spasmolytic Efficacy of 10 Pharmaceutical Agents Using Laser Speckle Contrast Imaging

Abstract: Background and Objectives: Vasospasm is a thorny problem often encountered in microvascular surgery that seriously threatens the survival of vascularized tissue transfers. This investigation is dedicated to establishing a model of vasospasm and to evaluating the antispasmodic efficacy of 10 pharmacologic agents. Study Design/Materials and Methods: Eighty Sprague-Dawley rats were used. After anesthesia and depilation, the femoral neurovascular bundle was exposed, and a pair of microsurgical forceps were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Their study revealed the onset of the effect within 2 min, with a sustained effect for up to 20 min, surpassing the potency of papaverine and magnesium sulfate. Ma et al [ 41 ] demonstrated a significantly shortened relaxation time from vasoconstriction in mechanically induced rat femoral arteriovenous preparations with 10 mg/mL phentolamine drops compared with physiological saline. They also reported superior antispasmodic effects of 10% magnesium sulfate and 12% lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Their study revealed the onset of the effect within 2 min, with a sustained effect for up to 20 min, surpassing the potency of papaverine and magnesium sulfate. Ma et al [ 41 ] demonstrated a significantly shortened relaxation time from vasoconstriction in mechanically induced rat femoral arteriovenous preparations with 10 mg/mL phentolamine drops compared with physiological saline. They also reported superior antispasmodic effects of 10% magnesium sulfate and 12% lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…A high spatial resolution mode calculating the blood flow index through LSTCA (temporal algorithm) is used 26 . The relative value of perfusion through a transverse section of a vessel can be calculated using the formula: perfusion = diameter × perfusion intensity 27 …”
Section: Methodsmentioning
confidence: 99%